Tinjauan Hukum Islam Terhadap Tradisi Sebarin Dui’ dalam Resepsi Pernikahan Adat Masyarakat Kepulauan Seribu Jakarta - Nuraini Nuraini; Nuril Habibi (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2023)
Traditional wedding receptions in Indonesia are very diverse, it feels incomplete if a wedding celebration does not use the traditions or customs that apply in the area, such as the Sebarin Dui' tradition that applies in the middle of Pramuka Island Community, Seribu Islands Regency, Jakarta. This unique tradition is very interesting to discuss because the Sebarin Dui' tradition originates from a mixture of customs from other regions which then merged into the traditions and customs of the Thousand Islands Community. This research aims to find out how the Sebarin Dui' tradition is at the traditional wedding of the Thousand Islands Community, and to find out how Islamic Law views the Sebarin Dui' tradition at the traditional wedding reception of the Thousand Islands Community. This research uses qualitative or descriptive research, with data collection techniques using field research, namely through observation and interviews with research subjects or informants. The results of this research are that the Sebarin Dui' tradition at community wedding receptions on Pramuka Island, Panggang Island Village, Seribu Islands Regency, Jakarta is the Sebarin Dui' tradition which aims to express gratitude and share good fortune with local residents and to entertain the guests present. So the Sebarin Dui' tradition carried out by the people of Pramuka Island, Panggang Island Village, Seribu Islands Regency has fulfilled the requirements to become a tradition or 'Sahih Urf' (does not violate Islamic law or Sharia law).